KARAKTERISTIK TEPUNG TALAS VARIETAS BENTUL DAN SATOIMO HASIL FERMENTASI TERKENDALI DENGAN INOKULUM KOMERSIAL - Santi Dwi Astuti; Nuri Andarwulan; Dedi Fardiaz; Eko Hari Purnomo (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Taro is one of non-rice carbohydrate sources which is rich in dietary fiber and minerals, mainly potassium, magnesium, calcium, dan phosphorus. The objectives of this research were to obtain taro flour with high amylose content and various pasting properties for different food ingredients through controlled fermentation technology using commercial inoculums. There are two taro varieties studied, namely Bentul and Satoimo. The fermentation time conducted were 12, 24, 36, and 48 hours. The commercial inoculums added were NKL, Bimo CF, and Fermipan. The results showed that fermentation of taro with Bimo CF for 48 hours increase the amylose content (66.82% for Bentul variety and 61.08% for Satoimo). The growth of mold contributed to the increase in amylose content. Longer fermentation time increase the breakdown and final viscosity of Bentul taro flour, but decrease the same characteristics in Satoimo flour. Fermented bentul taro flour has amylograph pattern similar to type A, while Satoimo has type C. Fermentation using Bimo CF for 48 hours produced the highest final viscosity in Bentul taro flour (3405 cP) thus it is potential to be used as a filler in products processed at low temperature. Meanwhile Satoimo taro produced flour with lowest breakdown viscosity (0.75 cP), therefore it is potential to be used as a filler in products processed at high temperature.